Designing Communicative Competence-Based English as a Foreign Language Curriculum Development in Integrated Islamic Elementary Schools - Amalia, Taranindya Zulhi; Susanti, Rini Dwi (Institut Agama Islam Negeri Kudus, 2024)
This study investigates the implementation and design of English language curriculum development based on communicative competence in integrated Islamic primary schools. The data was taken from interviews, observation, and documentation techniques. The findings indicated that other parties, including the Olympic and competition procurement institutions, were involved in the development of the English language curriculum. English language teachers construct lesson plans under the supervision of the principal, guaranteeing fair execution. The Language Festival is a new design for developing communicative competence at the elementary school level through mentoring subject teachers as well as support from the school and parents. It is designed to demonstrate the richness and diversity of language and instruct and enlighten individuals interested in languages and cultures about the languages spoken worldwide. This kind of external institution involvement is important to increase students' enthusiasm in primary school. The challenges include adapting face-to-face and remote curriculums, internet networks, and school manual content. They are solved by maintaining qualifying time allotments, partnering with language experts, leveraging asynchronous media, updating handbooks, and training for teachers.